NRAS associated RASopathy and embryonal rhabdomyosarcoma. Issue 1 (7th November 2019) - Garren, Benjamin; Stephan, Mark; Hogue, Jacob S.
Abstract: RASopathies are a group of phenotypically overlapping disorders that arise from dysregulation of the RAS/MAPK pathway. These disorders include Noonan syndrome, Costello syndrome, cardiofaciocutaneous syndrome, and neurofibromatosis‐Type 1. While somatic mutations in the three human Ras genes ( KRAS, HRAS, and NRAS ) are a common finding in a variety of cancers, germline mutations in each of the these genes cause developmental RASopathy phenotypes with mutations in specific genes typically correlating with specific phenotypes. We present the case of a germline heterozygous NRAS mutation producing a severe phenotype involving embryonal rhabdomyosarcoma, severe intellectual disability, and numerous melanocytic nevi in addition to more typical manifestations of Noonan syndrome. Additionally, the specific p.G12R NRAS mutation in this case is a common somatic mutation in cancer cells, and analysis of previously reported NRAS ‐RASopathy cases suggests that mutations at traditionally oncogenic codons are associated with elevated cancer risk not present with mutations at other sites.